Is this the correct approach to this problem:
I tried induction.
This is what the professor said: Hint: Treat the cases n even and odd separately.
Inductive hypothesis:
n=a+b for n>6
Base case
Let n=7. Then 3+4=7 where 3,4 have a gccd of 1.
Induction Step
Induction Step:
Prove: n+1=a+b
Case 1: Let a be a+1. This is possible because a is in the natural numbers.
So a+b+1=n+1. By the inductive hypothesis n=a+b so we can substitute it. Therefore n+1=n+1.
Case 2: Let b be b+1.
This is symmetrical to case one.
No comments:
Post a Comment